اكثار نبات الصبار Aloe vera خارج الجسم الحي - حبيب, هديل مكي; العاني, طارق علي; العاني, نبيل خلف (Al-Nahrain Journal of Science, 2018)
Tissue culture techniques were used to propagate Aloe vera in Vitro. The study included sterilization of explants, multiplication, rooting of the crown and acclimatization. Results revealed that 0.1% HgCL2 for 5 minutes was effective for sterilization and gave 100% survival rate. MS medium supplemented with BA and NAA was used six different concentrations from each.During the initiation stage the best combination was BA at 5 mg/l and 1.0 mg/l NAA which produced 2.5 shoots/explants. The highest shoot length (20.25) mm was recorded at the combination of 3.0mg/l BAP and 1.0mg/l NAA. Number of shoots and shoot length produced by these two combinations were significantly different than others. The highest mean number of shoots at multiplication stage was 5.67 shoots with average length 29.85 mm. These values were obtained using the combination of 7.0 mg/l BA and 3.o mg/l NAA which was highly significant than that obtained by other combinations. At rooting stage, MS medium free of any plant growth regulators was the most effective for rooting, it produced 3.67 root/ explants with an average length 30.68 mm. During acclimatization, pots containing 1:3 peat-moss: loamy soil (v:v) was suitable for establishment, it showed 100% survival rate.